IL-17 and TNF-β: Predictive biomarkers for transition to psychosis in ultra-high risk individuals - Ouyang, Lijun; Li, David; Li, Zongchang; Ma, Xiaoqian; Yuan, Liu; Fan, Lejia; Yang, Zihao; Zhang, Zhenmei; Li, Chunwang; He, Ying; Chen, Xiaogang (Frontiers in Psychiatry, 2022)
Background: Dysregulation of immunity, such as levels of inflammatory factors, has been regarded as a sign of schizophrenia. Changes in cytokine levels are not only described in the early onset of disease, but also observed in ultra-high risk (UHR) individuals. This study aimed to investigate the potential of cytokines as biomarkers for psychotic disorders and in individuals at UHR of developing a psychotic disorder in the future. Methods: The Luminex liquid chip technology was used to detect the concentrations of Interferon-gamma (INF-γ), Interleukin (IL)-2, Interleukin (IL)-4, Interleukin (IL)-6, Interleukin (IL)-17, Interleukin-1beta (IL-1β), and Tumor Necrosis Factor-beta (TNF-β) in the plasma of all subjects. Meanwhile, the plasma level of Tumor Necrosis Factor-Alpha (TNF-α) was measured with the enzyme-linked immunosorbent assay (ELISA) kits. Then, the levels of these cytokines were compared among patients with Drug-naïve first-episode schizophrenia (FES; n = 40), UHR population (UHR; n = 49), and healthy controls (HCs; n = 30). Baseline cytokine levels were compared among UHR individuals who later transitioned (UHR-T; n = 14), those who did not transition (UHR-NT; n = 35), and HCs (n = 30). Results: Our analysis results showed that IL-1β levels were significantly higher in UHR group than HC group(p=0.015). Meanwhile, TNF-α concentration was significantly increased in FES group compared with HC group(p=0.027). IL-17(p=0.04) and TNF-β(p=0.008) levels were significantly higher in UHR-T group compared with UHR-NT group. Conclusion: In conclusion, our findings suggest that the immuno-inflammatory activation level is increased in the early stage of psychosis before psychotic conversion and the Drug-naïve FES. IL-1β and TNF-α are the representatives of the specific biomarkers for UHR and FES, respectively. IL-17 and TNF-β may be the potential selective predictive biomarkers for future transition in UHR individuals.